Should economists listen to educational psychologists? Some economics of student motivation - Jocelyn Donze; Trude Gunnes (Statistics Norway, Research Department, 2011)
This paper sheds light on the role of student motivation in the success of schooling. We develop a model in which a teacher engages in the management of student motivation through the choice of the classroom environment. We show that the teacher is able to motivate high-ability students, at least in the short run, by designing a competitive environment. For students with low ability, risk aversion, or when engaged in a long term relationship, the teacher designs a classroom environment that is more focused on mastery and self-referenced standards. In doing so, the teacher helps to develop the intrinsic motivation of students and their capacity to overcome failures.
Keywords: D03; I21; 330; Education; Student Achievement; Intrinsic and Extrinsic Motivation; Effort; Goal Theory.